2015
DOI: 10.1111/odi.12369
|View full text |Cite
|
Sign up to set email alerts
|

Sprouty2 inhibition promotes proliferation and migration of periodontal ligament cells

Abstract: Spry2 combined with bFGF and EGF stimulation reduced PDL cell migration and proliferation with inducing osteoblastic differentiation. These in vitro findings may provide a molecular basis for novel therapeutic approaches for establishing periodontal tissue regeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…In addition, previous studies in our laboratory have shown that sequestration of Spry2 induces ERK activation, proliferation, and osteogenesis in osteoblastic cells by basic FGF (bFGF) and epidermal growth factor (EGF) stimulation in vitro while suppressing ERK activation and cell proliferation in gingival epithelial cells 26. In addition, we found that Spry2 knockdown combined with bFGF and EGF stimulation increased periodontal ligament cell proliferation and migration, while it prevented osteoblastic differentiation27. Therefore, combined application of a Spry2 inhibitor, bFGF, and EGF may effectively facilitate the growth of the periodontal ligament and alveolar bone while preventing tooth ankylosis and blocking gingival epithelial down‐growth toward bony defects.…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…In addition, previous studies in our laboratory have shown that sequestration of Spry2 induces ERK activation, proliferation, and osteogenesis in osteoblastic cells by basic FGF (bFGF) and epidermal growth factor (EGF) stimulation in vitro while suppressing ERK activation and cell proliferation in gingival epithelial cells 26. In addition, we found that Spry2 knockdown combined with bFGF and EGF stimulation increased periodontal ligament cell proliferation and migration, while it prevented osteoblastic differentiation27. Therefore, combined application of a Spry2 inhibitor, bFGF, and EGF may effectively facilitate the growth of the periodontal ligament and alveolar bone while preventing tooth ankylosis and blocking gingival epithelial down‐growth toward bony defects.…”
Section: Introductionsupporting
confidence: 54%
“…In contrast, suppression of Spry2 expression enhanced ubiquitination and degradation of EGF receptors, resulting in decreased proliferation of gingival epithelial cells [26]. In addition, we also found that Spry2 siRNA promoted lamellipodia formation induced by the stimulation of bFGF and EGF via AKT/PI3K and Rac1 activation in PDL cells, thereby activating cell migration while suppressing osteoblastic differentiation [27]. Thus, Spry2 downregulation could benefit periodontal tissue regeneration by increasing the stimulation of growth factors.…”
Section: Discussionmentioning
confidence: 68%
“…; Tanaka et al . ). Six1 expression is known to be regulated by BMP, FGF, and WNT, at least in the pre‐placodal region (Ahrens & Schlosser ; Litsiou et al .…”
Section: Discussionmentioning
confidence: 97%
“…Since human PDLSCs may be a source of MSCs for cell therapy (Zhu & Liang 2015), manipulating the proliferation of PDLSC is required for producing sufficient number of stem cells (Zhu & Liang 2015). For example, applying secreted molecules, such as BMP4, FGF2, WNT3A, and WNT5A, forces DF stem/progenitor cells and PDLSCs to increase proliferation (Liu et al 2013;Xiang et al 2014;Yan et al 2014;Tanaka et al 2015). Six1 expression is known to be regulated by BMP, FGF, and WNT, at least in the pre-placodal region (Ahrens & Schlosser 2005;Litsiou et al 2005).…”
Section: The Role Of Six1 In Regulating Dfc and Pdlc Proliferationmentioning
confidence: 99%
“…In our recent study entitled "Sprouty2 inhibition promotes proliferation and migration of periodontal ligament cells", we demonstrated that Spry2 depletion by bFGF and EGF stimulation markedly enhanced PDL cell proliferation and migration [24]. Spry2 knockdown increased bFGF and EGF-induced ERK activation and proliferation in PDL cells, and increased cell migration in a scratch wound-healing assay and Boyden chamber migration assay.…”
Section: Introductionmentioning
confidence: 99%